2018
DOI: 10.1177/0300060518793039
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of reporting fatty liver on ultrasound in asymptomatic patients during routine health checkups

Abstract: ObjectiveUltrasonography is an efficient technique for detecting fatty liver. Its sensitivity and specificity in detecting moderate to severe fatty liver are comparable to those of histology. Fatty liver is associated with abnormal lipid and lipoprotein metabolism and insulin resistance, metabolic syndrome, cardiovascular/renal disease, type 2 diabetes, and other conditions. This study was performed to compare the serum lipid profiles and serum glutamic pyruvic transaminase (GPT), glutamic oxaloacetic transami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 18 publications
(36 reference statements)
0
22
0
2
Order By: Relevance
“…6 In their study Mahale et al reported the mean age of 49.73 years. 7 The majority of the cases in our study were in the age group 40 to 60 years. Similar findings were also reported in their study by Khanal et al, where majority of patients belonged to age group of 50-59 (32.1%), followed by 40-49 (28.8%).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…6 In their study Mahale et al reported the mean age of 49.73 years. 7 The majority of the cases in our study were in the age group 40 to 60 years. Similar findings were also reported in their study by Khanal et al, where majority of patients belonged to age group of 50-59 (32.1%), followed by 40-49 (28.8%).…”
Section: Discussionmentioning
confidence: 71%
“…But Ultrasound, ALT and AST showed no correlation with fibrosis score. 6 High serum ALT and AST levels were seen in 13.8% and 35.5% cases of NAFLD respectively in their study by Mahale et al 7 However these results were not statistically significant.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The prevalence of NAFLD varies widely; it affects approximately 25% of individuals across the globe (7,8). Its relatively high prevalence even in apparently healthy Turkish individuals underlines the importance of early recognition of MAFLD in daily clinical practice (9)(10)(11)(12). Unfortunately, early diagnosis of MAFLD constitutes a major clinical challenge owing to its usually asymptomatic presentation.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that metabolic comorbidities interrelated with NAFLD include obesity, type 2 diabetes mellitus (T2DM), hypertension, hyperlipidemia and metabolic syndrome [2]. NAFLD represents a series of diseases ranging from non-alcoholic fatty liver (simple steatosis) thorough non-alcoholic steatohepatitis (NASH) to different stages of brosis, nally cirrhosis hepatocellular carcinoma, and terminal liver failure [7][8][9]. Currently, the obesity epidemic in the world is leading to a sharp increase in NAFLD, which is expected to lead to an increase in clinical and economic burden [10].…”
Section: Introductionmentioning
confidence: 99%